2021
DOI: 10.1002/int.22446
|View full text |Cite
|
Sign up to set email alerts
|

Deep semi‐supervised classification based in deep clustering and cross‐entropy

Abstract: Self‐labeled techniques, a semi‐supervised classification paradigm (SSC), are highly effective in alleviating the scarcity of labeled data used in classification tasks through an iterative process of self‐training. This problem was addressed by several approaches with different assumptions about the features of the input data, examples of these approaches being self‐training, co‐training, STRED, among others. This paper presents a framework for data self‐labeling based on deep autoencoder combined with a self‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…Different gradient descent optimisation techniques such as RMSProp, Adamax [ 13 ], and Adam are commonly used to address computational complexity problems. Deep autoencoder [ 14 ] is used to reduce the dimensionality of the input in a labelling layer [ 15 , 16 ]. Most machine learning methods have convergence issues towards the global minimum.…”
Section: Introductionmentioning
confidence: 99%
“…Different gradient descent optimisation techniques such as RMSProp, Adamax [ 13 ], and Adam are commonly used to address computational complexity problems. Deep autoencoder [ 14 ] is used to reduce the dimensionality of the input in a labelling layer [ 15 , 16 ]. Most machine learning methods have convergence issues towards the global minimum.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Gated recurrent units (GRUs) and long short-term memory (LSTM) are some of the widely used recurrent neural network (RNN) methods for different time series predictions. 33,34 Different variations in parameters and combinations of various hybrid approaches are tested to improve the prediction accuracy. de Lima et al 33 used a deep NN model utilising stock data and transaction records to predict future intervals.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Different variations in parameters and combinations of various hybrid approaches are tested to improve the prediction accuracy. de Lima et al 33 used a deep NN model utilising stock data and transaction records to predict future intervals. The analysis results revealed that bidirectional LSTM could accurately forecast stock prices for the economic selection process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation